Material Selection to Modeling: A Comprehensive Investigation of a Conformal Circularly Polarized Textile Antenna for Wearable Applications - D. Ram Sandeep; S. Salma; K. Sanjay Kumar; P. Rakesh Kumar; Satti Sudha Mohan Reddy; Kokku Aruna Kumari; Sanjay Bandi; B. T. P. Madhav (IEEE Access)
This study presents a comprehensive investigation into the design, material selection, and performance evaluation of a conformal circularly polarized textile antenna tailored for wearable applications. This study involves in-depth surface morphology analyses using Scanning Electron Microscopy (SEM) and Optical microscopy on various textile substrates. In the process of investigation, it was found that felt has the desired qualities to make a suitable substrate with good flexibility, skin-friendly nature, and exhibits excellent mechanical properties. Through the application of Energy Dispersive X-ray Spectroscopy (EDS) and flexibility investigation, nano-silver conductive paste deposition was established as superior in both conductivity and flexibility. The substrate with the size of $40× 30× 1.5$ mm3 is used in the design of the multiple-band circularly polarized antenna which covers LTE, LoRa, 5G, FWA, and ISM applications at 1.7, 2.4, 3.8, 4.6, and 5.2 GHz, correspondingly. The antenna operates with a gain value of 6.19, 6.95, 7.53, 8.29, and 9.16 dBi and an efficiency ranging between 85-90% in the operating frequencies. To test the antenna in a more realistic condition, mechanical bending tests were performed from 0° to 60° in vertical and horizontal planes. The unique circular polarization characteristics of the antenna were also confirmed with bending, exhibiting stability in axial ratio performance and polarization purity. Specific Absorption Rate (SAR) analysis was conducted by placing the textenna at various positions on the human phantom model, and all values remained within the safety limit of 1.6 W/kg. The results confirm that the proposed antenna offers excellent flexibility, robust performance, and reliable operation for body-centric wearable communication systems.